Clinical management of terminal Kennedy ulcer: literature review (Research, Society and Development, 2024)
Objective: To develop a clinical guide for the management of Kennedy Terminal Ulcer (KTU) based on a critical analysis of the scientific literature. Methodology: Integrative literature review, guided by the question "How is the clinical management of KTU performed?" The databases used were PubMed, LILACS (Latin American and Caribbean Health Sciences Literature), BDENF (Nursing-specific database), and SciELO. The inclusion criteria adopted were: full articles on the subject available in Portuguese, Spanish, and English. Results and discussion: Among 30 studies found, 16 were analyzed, in which KTU was identified as a rapidly progressing wound, different from a pressure ulcer, that advances in staging within a few hours or days, often leading to death. Thus, the clinical management found in the literature was palliative wound care, focusing on symptom management such as pain, odor, excessive exudate, and bleeding, without aiming for wound healing. This management should reduce suffering and improve the patient's quality of life. It is worth noting that, regardless of the patient's clinical situation, the prevention of injuries must be maintained. Conclusion: The study preliminarily concluded that the scarcity of content on the subject still leads to a lack of knowledge among professionals regarding management; therefore, this study may provide guidance on the correct diagnoses and clinical management of patients with Kennedy Terminal Ulcer.